Pengaruh Kemampuan Teknik Personal, Pelatihan dan Pendidikan terhadap Efektivitas Penggunaan SIA Pada Rumah Sakit - Turnip, Tellycia Ruth; Suardhika, I Made Sadha (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p22, 2018)
The purpose of this study is to determine the effect of personal technical skills, training and education on the effectiveness of the use of accounting information systems. The population in this study were 9 hospitals in Badung regency and 9 samples of hospital determined by saturated sample method. Respondents in this study amounted to 63 employees. Data collection was done by interview and questionnaire. Data analysis technique used is with multiple linear regression.The results of this study indicate that the variable of personal technique ability has a significant positive effect on the effectiveness of the use of accounting information system, this means that if the high personal technique skills then the effectiveness of the use of accounting information system will be high, and training and education variables significant positive effect on the effectiveness of the use of accounting information system , this means that the more employees participate in training and education then the effectiveness of the use of accounting information systems will increase. Keywords: Ability of personal technique, training and education, effectiveness of accounting information system usage.